IMPLEMENTASI PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENINGKATKAN KEMAMPUAN MENGANALISIS KERAGAMAN ALAM INDONESIA PADA PEMBELAJARAN IPS - Erli Ananda Runikasari; Nuansa Bayu Segara; Dwi Murwanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study examines the implementation of the Discovery Learning model based on Culturally Responsive Teaching (CRT) to enhance students' analytical skills regarding Indonesia's natural diversity in Social Studies at SMP Negeri 1 Surabaya. The combination of CRT and Discovery Learning is expected to link the material with students' cultural backgrounds, improving their engagement and understanding. This Classroom Action Research was conducted in two cycles, with two learning sessions in each cycle. Data were collected through observation and tests, showing an increase in learning mastery from 48.57% in the first cycle to 85.71% in the second cycle. These results confirm the effectiveness of this method in enhancing students' understanding.